Praktik Jual Beli Makanan Sushi dengan Sistem Konsinyasi Perspektif Hukum Positif dan Hukum Islam (Studi Kasus di Rumah Produksi Sushi in Kecamatan Larangan Kota Tangerang) - Ragil Sapto Aji Nugroho; Irvan Iswandi (Journal on Education, 2023)
Long time ago, if someone wants to run a business, he/she must prepare and has all resources started from the capital, product, business place, until the marketing strategy. Now all of those is not needed anymore. A businessman can just prepare the product only, without business place in order to display their product and vice versa because the sellers can intertwine cooperation among them in selling the product with console system. This research was conducted at Sushi in Production House which is a culinary company. This research investigated, first; how is the practice of sushi food commerce withs its console system at Sushi in production house, second; how is the positive legal perspective and Islamic law perspective towards the practice of sushi commerce with its console system. Analysis technique used in this research was descriptive analysis and data obtained were from literature study and analyzed qualitatively. Data collection was conducted through interview, observation, and documentation. The purpose of this research is to know the positive legal perspective and Islamic law perspective towards the practice of sushi food commerce with its console system at sushi in production house at Larangan District Tangerang City. The research results in the field show that the practice of sushi commerce at Sushi in production house with its console system has been in line with the positive legal perspective and Islamic law. This can be seen from the agreement applied by using Wakalah bil ujrah agreement.